Influence of distinct reinforcing schemes on the shear ressistance of masonry - Vasconcelos, Graça (2012)
One of the major concerns about the use of unreinforced masonry in seismic prone regions is its inadequate behavior under seismic loads, which has been shown from recent earthquakes. If fact, it has been seen that unreinforced masonry buildings present commonly considerable in-plane damage, which is associated to the low shear resistance of unreinforced masonry and to low capacity to dissipate energy. The improvement of the overall behavior of structural masonry under shear can be achieved by the addition of horizontal and vertical reinforcement. Tgis paper presents the results of a series of diagonal compression tests carried out on concrete block masonry with distinct types of reinforcement’s arrangements. It was seen that the better configuration for the reinforcement arrangement is the combination of vertical and horizontal reinforcements leading simultaneously to the improvement of shear strength and ductility.